2022
DOI: 10.14740/jem823
|View full text |Cite
|
Sign up to set email alerts
|

Obesity Measurement Index Is Associated With Hemoglobin A1c Level in Young Adult Without Diabetes: A Single-Center Cross-Sectional Study

Abstract: Background: Obesity is a public health problem in the world, which can lead to several risks of cardiovascular events, such as, diabetes mellitus type 2 and respiratory disorders. This study aimed to analyze the obesity measurements index and hemoglobin A1c (HbA1c) in young adults without diabetes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…Obesity can affect the level of HbA1c. There was a significant correlation between anthropometric measurements and HbA1c, with HbA1c levels being higher in the obese group, and significant patient scores with HbA1c and high body fat indicate the relationship of the molecule with obesity 13 . Our data also support these findings.…”
Section: Discussionmentioning
confidence: 88%
“…Obesity can affect the level of HbA1c. There was a significant correlation between anthropometric measurements and HbA1c, with HbA1c levels being higher in the obese group, and significant patient scores with HbA1c and high body fat indicate the relationship of the molecule with obesity 13 . Our data also support these findings.…”
Section: Discussionmentioning
confidence: 88%
“…Regarding ALB-g, the primary observations indicated a negative correlation with fat (DXA), both in grams (for the entire sample and DM2 group) and as a percentage in DM2 postmenopausal women. The inverse relationship between ALB-g and fat mass has been established in previous studies [ 37 , 38 ], and it has been recognized as a reliable measure for monitoring glycemic control in individuals with diabetes over a moderate period of time [ 39 ]. In the present study, we observed that postmenopausal women with diabetes exhibited elevated levels in circulation, as shown in Figure S1 Supplementary (only included for the discussion section).…”
Section: Discussionmentioning
confidence: 99%
“…Excess fat cells, over time, will cause fat cells to become resistant to insulin's antilipolytic actions, resulting in an increase in the process of lipolysis and free fatty acids in plasma. Free fatty acids boost gluconeogenesis resistance, which then triggers insulin in the liver and muscles (Sarnings et al, 2022). However, in patients with type 2 diabetes mellitus, higher BMI and WC were linked to increased insulin resistance and lower insulin sensitivity (Deusdará et al, 2022;Zhao et al, 2017).…”
Section: Discussionmentioning
confidence: 99%